AWARENESS OF MAL CRIME IN ISLAM AMONG UITM STUDENTS - Muhammad Azib Bin AB Manaf; Farah Safura Muhammud (Journal of Islamic, Social, Economics and Development, 2022)
Mal crime is one of the common cases in Malaysia, those are theft, robbery, burglary and including cybercrime. The statistics of property crime in 2019 released by the Department of Statistic Malaysia is 66,967 cases. The problem is how aware people in Malaysia are about this issue. So, this study conducted on UiTM student to find out the awareness of Mal crime among 100 UiTM students them following with three objectives which are to identify the concept of Mal crime in Islam among UiTM students, to discuss the factor of Mal crime among UiTM student, and to ensure the awareness of Mal crime. Research methodology used in this study is a quantitative method by answering a questionnaire with a linear scale. This research found out the awareness of mal crime among UiTM students is high. However, a lot campaign should be done because the cases regarding property is increasing especially during COVID-19 pandemic